Septic arthritis following joint injections: a 17 years retrospective study in an Academic General Hospital. - Larghi, Marco Mattia; Grassi, Miriam; Placenza, Emanuele; Faugno, Luca; Cerveri, Pietro; Manzotti, Alfonso (Acta Biomedica Atenei Parmensis, 2022)
Background:Septic arthritis following intra-articular infiltrations is an uncommon devastating complication correlated  to high costs for the health service and often to poor outcomes. The purpose of this study is to assess a 17-years experience in a single academic multispecialist hospital managing this uncommon complication in Orthopaedic practice.Methods:Patients with diagnosis of septic arthritis following joint injections treated in our hospital from January 2002 to December 2019 were included in the study. Clinical and demographic data, pathogens, injected agent, conservative/surgical treatments were reviewed. Patient were classified according to the ore operative Charlson Comorbidity Index (CCI) and the Cierny-Mader Classification(CMC). Furthermore follow-up outcome and time occurred to infection eradication were registered.Results:We included in the study 11 patients with a median age of 74 years old (IQR= 61.5 - 79). The median CCI was 3  (IQR= 2 - 5) and the majority of patients belong to CMC = B class. Septic arthritis occurred mainly following corticosteroids injections and more frequently involving knees. The pathogen more often isolated was Staphylococcus aureus. Five (45%) patients referred an history of multiple intrarticular injections. 7 patients (64%) had a complete resolution following an arthroscopic debridement, 4 (36%) patients underwent to a 2-stage replacement and one of them hesitated in an arthrodesis because of a recurrent periprothesic joint infection and extensor apparatus insufficiency.Conclusion:The authors observed a potential increased risk of septic arthritis following joint injection in patients with history of multiple injections and poor health/immunological conditions. They recommend an early arthroscopic debridement as the treatment of choice especially in septic knees  performed in a multispecialist dedicated center